Nalar Komunikasi Spiritual dalam Membentuk Kepribadian Muslim (Sebuah Kajian Tasawuf) - Mustain Fitri (UMSU, 2022)
Spiritual communication is communication with God. Allah created many symbols and signs; qur'aniyah and kauniyah, so that humans can understand the Divine message created by Him. That is, between humans and God there is a substantial interaction in building communication. The tip of the intensity of spiritual communication to Allah is the formation of a Muslim personality. Therefore, the purpose of this study is to explain the reasoning of spiritual communication in shaping Muslim personalities from the perspective of Sufism. This type of research is qualitative. This qualitative use is based on the descriptive characteristics of this research. Data obtained documentation of scientific works (books and journals) that discuss spiritual communication and Sufism. The results of this study indicate that through intense patterns of spiritual communication will emerge Muslim personalities such as repentance, asceticism and patience, which can become symbols of human Sufi maqamat.